Thrombocytopenia and Community-acquired pneumonia: A comparative analysis at a teaching Hospital - Sachin Chaudhary,; Dharma Datta Subedi,; Hari Narayan Purbey,; Ram Narayan Mandal, (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives Community Acquired Pneumonia (CAP) continues to be a significant cause of morbidity and mortality worldwide, especially in at-risk populations. There have been only some recent publications focusing on hematological parameters and how they correlate with clinical outcome, such as thrombocytopenia. This study aimed to investigate the association between thrombocytopenia and CAP severity, as well as the predictive value of other clinical markers such as leukocyte count, duration of hospital stays, and CURB-65 score. Materials and Methods: An analytical observational study with a prospective cross-sectional design was conducted on patients diagnosed with CAP at JMCTH from October 2023 to Sep 2024. Patient’s data were extracted from medical records. The correlation between the platelet count and CAP severity was analyzed. Results: A total of 102 cases were collected. Number of patients diagnosed with CAP was found to be 100%. Males 59 (57.8%) were more affected compared to females 43 (42.1%). Patient ages ranged from 16 to 75 years old. Mild thrombocytopenia was 9(8.8%), moderate thrombocytopenia 49(48%), severe thrombocytopenia 44(43%) was observed. Patients with >65 years had highest prevalence of thrombocytopenia 25(24.5%)). Similarly in terms of leukocytosis, it was found to be mild 43(42%), moderate 50(49%), severe 9(8.8%) respectively. Regarding severe thrombocytopenia 2(66.67%) participants were expired and in severe leukocytosis 2(66.67%) were expired which was statistically significant p value is <0.001. Also, CURB-65 score having >3, indicates the higher mortality rate which is statistically significant, p value < 0.001. Hospital stay was more than 14 days were 9(8.8%), where 2(66.67%) expired which was also statistically significant and p value < 0.001. Conclusion: The significance of thrombocytopenia and other clinical indicators as they relate to the prognosis of CAP, and paves the way for novel interventions and individualized therapies.